3 - Traditional Cultural Practices of Imparting Sex Education and the Fight against HIV/AIDS: The Case of Initiation Ceremonies for Girls in Zambia - Augustus K. Kapungwe (African Sociological Review, 2004)
The Human Immuno-Deficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) have become a major health problem in Zambia. Because of the threat HIV/AIDS poses to the nation, the government of Zambia embarked on a public health campaign aimed at combating the scourge. However, so far this campaign has predominantly been conducted through modern channels of information communication. The overall objective of this study was to explore the role one particular traditional channel of sex information communication, the initiation ceremony of girls, could play in disseminating information to combat HIV/AIDS. Data were collected from five residential areas using systematic random sampling. Overall, the study concludes that although there is no evidence to directly link initiation ceremonies with HIV/AIDS, indirectly today’s initiation ceremonies enhance the spread of HIV/AIDS. But it is encouraging to point out that, given the demonstrated willingness of the majority of initiators to learn more about HIV/AIDS, the identified inadequacies in initiation ceremonies can be removed so that this channel is used effectively in the fight against the disease.